New complex phosphates Cs3MIIBi(P2O7)2 (MII – Ca, Sr and Pb): synthesis, characterization, crystal and electronic structure. Issue 7 (24th January 2018) - Zatovsky, Igor V.; Strutynska, Nataliia Yu.; Hizhnyi, Yuriy A.; Baumer, Vyacheslav N.; Ogorodnyk, Ivan V.; Slobodyanik, Nikolay S.; Odynets, Ievgen V.; Klyui, N. I.
Abstract : New phosphates Cs3 M II Bi(P2 O7 )2 (M II – Ca, Sr and Pb) with the original framework topology are discussed as prospective hosts for luminescent ions. Abstract : Herein, the peculiarities of complex phosphate formation in self-fluxes of Cs–M II –Bi–P–O (M II = Ca, Sr, Ba and Pb) systems with Cs/P = 0.7–1.3 at fixed ratios of Bi/P = 0.2 and Bi/M II = 1.0 were studied and discussed. Three novel isostructural diphosphates with the general composition Cs3 M II Bi(P2 O7 )2 (M II = Ca, Sr and Pb) and the original framework topology were synthesized and characterized via single-crystal and powder X-ray diffraction, SEM, DTA, and FTIR- and UV-VIS-spectroscopy. In addition, electronic structure (DFT) and Voronoi–Dirichlet polyhedra (VDP) characteristics calculations and crystallochemical analysis were performed. In the structure of the new compounds, the M II O7 and BiO6 polyhedra are connected via common oxygen vertices forming infinite helical-like chains, which are linked by P2 O7 groups into a 3D-framework with pentagonal tunnels, where the Cs + cations are located. The structural peculiarities are discussed considering perspectives for the creation of new luminescent materials. The dielectric bandgaps, E g, of the Cs3 M II Bi(P2 O7 )2 crystals reveal an ∼0.2 eV low-energy shift in the Ca–Sr–Pb sequence of M II cations, which reveals the possibility to tune the optical absorbance spectra of the crystals via the synthesis of solid solutions with various contents of M II cations. The glass-ceramic synthetic approach is also proposed as a convenient method for the creation of new diphosphates, and the applicability of this method is verified for Cs3 CaBi(P2 O7 )2 .